Assessment of Empathy Levels among Medical Students at International Medical University Post-Pandemic Using the Jefferson Scale of Empathy-Student Version - Goh Lay-Khim; Rashieqah Nadhierah Nor Yusof’Ain; Normy Binti Narihan (Asian Journal of Medicine & Health Sciences, 2024)
The ability to be empathetic is the crucial component that leads to successful doctor-patient communication. The Movement Control Order (MCO) implemented during the COVID-19 outbreak has significantly affected the curriculum, particularly by limiting exposure to clinical settings with real patient encounters. This study aimed to examine the level of empathy among medical students at International Medical University (IMU) in the post-pandemic period. A cross-sectional study using the Jefferson Scale of Empathy-Student version (JSE-S) questionnaire was conducted. A total of 302 medical students, spanning both pre-clinical years (Semesters 1 to 5) and clinical years (Semesters 6 to 10), participated in the study. The mean empathy score was 110.90. Findings revealed significant associations between empathy scores and demographic factors, such as nationality (p = 0.010) and year of study (p = 0.028). The study also found significant associations between compassionate components and demographics, such as gender (p = 0.016), nationality (p = 0.046), and year of study (p = 0.030). No significant differences were found between pre-clinical and clinical years, suggesting that training via remote mode with simulated and real patients, without no exposure to clinical settings, potentially contributed to these results.